Children’s Everyday Creativity at School as an Inspiration for Action Research on Education of Pedagogy Students - Paszenda, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The study is a presentation of the author’s research project. It concerns a critical analysis of the everyday school life of a child at a younger school age and of pedagogy students as candidates for primary education teachers, in the context of shaping their creative skills.The analysis revealed the short comings of the Polish education system and its ineffectiveness in the area of shaping the creative skills of pupils and students. This gloomy diagnosis prompted the author to undertake qualitative research based on the action research method. The entire research process was carried out in accordance with the theoretical, practical and social research objectives formulated (before and during the research). The main goal of the research was to develop the professional skills of pedagogy students through thepractical implementation of 30-hour classes in creative thinking and action training and to examine the relationship between participation in training and acquiring professional skills. The results of the research showed that the mastery of creative skills by future educators may be the basic factor of their professional success.
Keywords: everyday school life; creativity; action research; professional preparation; teacher training